Investigation of Quality and Patient Safety Courses Conducted in Undergraduate Nursing Programs in Turkey - Sevda Arslan; Gulden Basit (Association of Nurse Managers, 2021)
Aim: This study aimed to determine some characteristics of quality and patient safety courses in the undergraduate nursing curriculum of active nursing departments of the state and private universities in Turkey. Method: This descriptive and cross-sectional study was conducted from September-October 2020. One hundred and fifty active undergraduate nursing programs of state and private universities in Turkey constituted the study population. The evaluation form created by the researchers was used as a data collection tool. The data were analyzed using descriptive statistics. Results: It was determined that 58.66% of universities had courses on quality or patient safety courses. However, 87.92% of the academic staff who conducted the courses had no expertise in nursing management. It was determined that the contents of the courses had a limited value in developing knowledge, attitudes and skills in undergraduate nursing students. Conclusion: It was determined that most nursing undergraduate curriculum had a course on quality or patient safety, but the contents of the existing courses failed to establish standards for quality service and patient and employee safety in providing nursing care. The courses should contain current issues the student needs which can be used in the actual working environment and be transferable to the clinical practice.